Planning to improve the quality of public services using servqual and Quality Function Deployment integration - Anis Saleh; Yan Herdianzah; Andi Pawennari; Arfandi Ahmad (Operations Excellence: Journal of Applied Industrial Engineering, 2023)
Service is any activity that is intended or intended to provide satisfaction to customers, but in fact, there are still several service systems that are always complained about by the community, including the problem of family cards (KK) and identity cards (KTP) because these services are the most dominant in the Sepee District Office. This study aims to obtain the quality of service in the district so that it can be repaired or improved the service system. This study uses the integration of Service Quality (Servqual) with a 5-dimensional approach to service quality, namely Tangibles, Reliability, Assurance, Responsive, and Empathy with the integration of Quality Function Deployment (QFD) to create a development and planning process in setting specifications for community needs and evaluating strengths and weaknesses on the service process. The results of Servqual and QFD integration in this study can be seen from the Q value which is not in accordance with service quality standards, the Q value shows 0.86 meaning that service quality cannot be said to be good because 0.86 ≤ 1. Based on the Cartesian diagram, 8 attributes are found. In quadrant A high-expectation value and low-performance value). According to the community, the highest attribute whose perceived value is low but whose expectation value is high is that service facilities and infrastructure are complete and sophisticated.